Comparison of Loneliness and Social Skill Levels of Children with Specific Learning Disabilities in Terms of Participation in Sports - Atike Yılmaz; Hüseyin Kırımoğlu; Fikret Soyer (Education Sciences, 2018)
This study was conducted in order to compare loneliness and social skill levels of children with specific learning disabilities in terms of participation in sports. For this study, a screening model was used. The study group was composed of 56 children who were aged between 7 and 14 years and diagnosed with a specific learning disability (30 boys and 26 girls). “Personal Information Form”, “Children’s Loneliness Scale”, “Matson Evaluation of Social Skills with Youngsters (MESSY)” were used in this study. For the data processes and data analyses, SPSS 22 was used. According to the test of normality, non-parametric tests were employed for those data that did not follow a normal distribution and the correlations among variables were tested with correlation analysis at p < 0.05 while differences among variables were tested with Mann–Whitney U and Kruskal–Wallis tests at p < 0.05. According to the findings obtained in this study, there were no significant differences in terms of sex, the number of family members and the number of brothers and sisters while there were significant correlations in terms of age, sports status, MESSY-subscales and loneliness. In sum, it may be concluded that sports played a positive role in social skill and loneliness levels among children with specific learning disabilities.